2022
DOI: 10.1177/09697330221122905
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress and spiritual/religious orientation: Moral agency, norms and resilience

Abstract: Background Nurses tasked with providing care which they perceive as increasing suffering often experience moral distress. Response to moral distress in nurse wellbeing has been widely studied. Less research exists that probes practicing nurses’ foundations of moral beliefs. Aims The purpose of this phenomenological study was to gain understanding of nurse meaning-making of morally distressing situations, with particular attention to ethical norms, moral agency and resiliency, and nurse religious/spiritual orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…On the other hand, five articles (n = 5) were published in 2021 (Smallwood et al 2021;Donkers et al 2021;Patterson et al 2021;Hines et al 2021;Zerach and Levi-Belz 2021), and they account for 31% of the included studies. For 2023, two studies (n = 2) were identified (Kok et al 2023;Koonce and Hyrkas 2023), representing 13% of the included studies. The studies were conducted from December 2019 (Kok et al 2023) till February 2022 (Gherman et al 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, five articles (n = 5) were published in 2021 (Smallwood et al 2021;Donkers et al 2021;Patterson et al 2021;Hines et al 2021;Zerach and Levi-Belz 2021), and they account for 31% of the included studies. For 2023, two studies (n = 2) were identified (Kok et al 2023;Koonce and Hyrkas 2023), representing 13% of the included studies. The studies were conducted from December 2019 (Kok et al 2023) till February 2022 (Gherman et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The research methods used in the studies were as follows: quantitative design studies (n = 8) (Asadi et al 2022;Smallwood et al 2021;Donkers et al 2021;Hines et al 2021;Zerach and Levi-Belz 2022;Gherman et al 2022;Maffoni et al 2022;Kok et al 2023) (Koonce and Hyrkas 2023); and in four cases (n = 4), the theoretical framework of the study was not mentioned (Patterson et al 2021;Zerach and Levi-Belz 2021;Gherman et al 2022;Hegarty et al 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, constant exposure to morally challenging situations can leave individuals feeling hopeless and questioning the point of striving for ethical behavior. This can make it di cult to nd meaning in work and decrease overall moral resilience [33,53,54].…”
Section: Main Ndingsmentioning
confidence: 99%